2010
DOI: 10.1152/ajpcell.00269.2009
|View full text |Cite
|
Sign up to set email alerts
|

Blebbistatin, a myosin II inhibitor, suppresses contraction and disrupts contractile filaments organization of skinned taenia cecum from guinea pig

Abstract: To explore the precise mechanisms of the inhibitory effects of blebbistatin, a potent inhibitor of myosin II, on smooth muscle contraction, we studied the blebbistatin effects on the mechanical properties and the structure of contractile filaments of skinned (cell membrane permeabilized) preparations from guinea pig taenia cecum. Blebbistatin at 10 microM or higher suppressed Ca(2+)-induced tension development at any given Ca(2+) concentration but had little effects on the Ca(2+)-induced myosin light chain pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 40 publications
1
19
1
Order By: Relevance
“…This agent strongly inhibited most vertebrate striated muscle- and non-muscle myosin II ATPase activities (2) as well as vertebrate smooth muscle myosin (SMM) ATPase activity (3, 4). Several groups, including us, have also found that blebbistatin inhibited the smooth muscle preparations and smooth muscle cell contraction at around 10 μM (3,4,5,6,7). The inhibitory mechanism on the actin-myosin interaction has been thought to be due to inhibition of myosin ATPase resulting in interference of cross-bridge cycling (1, 2).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…This agent strongly inhibited most vertebrate striated muscle- and non-muscle myosin II ATPase activities (2) as well as vertebrate smooth muscle myosin (SMM) ATPase activity (3, 4). Several groups, including us, have also found that blebbistatin inhibited the smooth muscle preparations and smooth muscle cell contraction at around 10 μM (3,4,5,6,7). The inhibitory mechanism on the actin-myosin interaction has been thought to be due to inhibition of myosin ATPase resulting in interference of cross-bridge cycling (1, 2).…”
Section: Introductionmentioning
confidence: 85%
“…The inhibitory mechanism on the actin-myosin interaction has been thought to be due to inhibition of myosin ATPase resulting in interference of cross-bridge cycling (1, 2). Also previous studies have indicated that conformational change of SMM by blebbistatin spatially interferes with the actin-myosin interaction of smooth muscle cells (4, 5, 7). Blebbistatin simultaneously inhibited F-actin-SMM interaction, force development and organization of contractile filaments in skinned smooth muscles of the guinea pig taenia cecum (5).…”
Section: Introductionmentioning
confidence: 91%
“…Whole cell FRET analysis, as presently employed, has been used successfully to evaluate protein-protein interactions in smooth muscle cells (32,33,36). Because the donor/acceptor must be within 10-nm distance from each other for efficient energy transfer (37,38), this technique provides a measure of protein-protein distances compatible with molecular interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Inclusion of nuclear staining of MLCK in the A7r5 cell did not affect the significance of the results presented herein (data not shown). The quantification by FRET using this experimental protocol was described previously (31,32).…”
Section: Confocal/fret Microscopymentioning
confidence: 99%
“…Inhibitors of myosin function have been described previously (Watanabe et al, 2010). A direct inhibitor of SMM would be attractive for reducing arterial pressure through peripheral vasodilation.…”
Section: Introductionmentioning
confidence: 99%